2021
DOI: 10.1093/geroni/igab015
|View full text |Cite
|
Sign up to set email alerts
|

Network-Exposure Severity and Self-Protective Behaviors: The Case of COVID-19

Abstract: Background and Objectives To clarify whether awareness of the extent and severity of exposure to the coronavirus disease 2019 (COVID-19) virus in the social networks of older adults is related to the engagement by the latter in self-protective behaviors. The inquiry is guided by the Health Belief Model and by concepts from the domain of social networks. Research Design and Methods Data from the Survey of Health, Ageing and Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Future research should consider using social network analysis to study smaller networks than our national study. Such research would assess if and how the COVID-19 protective behaviors documented in our study are interrelated within social networks, as documented in Litwin and Levinsky's research with an older population [34] and as suggested by socio-physical model theory.…”
Section: Discussionmentioning
confidence: 88%
“…Future research should consider using social network analysis to study smaller networks than our national study. Such research would assess if and how the COVID-19 protective behaviors documented in our study are interrelated within social networks, as documented in Litwin and Levinsky's research with an older population [34] and as suggested by socio-physical model theory.…”
Section: Discussionmentioning
confidence: 88%
“…The first two indicators are categorized as “mild” and the two last ones as “severe.” Multiple answers are assigned according to the most severe response category. Since Litwin and Levinsky (2021) show that self-exposure and network-exposure are similarly associated with protective behavior in terms of direction, significance, and magnitude, we do not distinguish between these two types of exposure.…”
Section: Methodsmentioning
confidence: 96%
“…While the main motivating factor among younger people is a pro-social orientation ( Franzen & Woehner, 2021 ), the motivation to self-protect increases with age because most older people perceive themselves as more vulnerable and at risk ( Brug et al, 2004 ; Jørgensen et al, 2021 ; Yıldırım et al, 2021 ). Distinguishing between older age groups can be useful since other studies (e.g., Litwin & Levinsky, 2021 ; Pasion et al, 2020) even found that the oldest age group (age 70 or more) reported lower perceived risk and showed less protective behavior compared with younger old people (age 60–69).…”
Section: Introductionmentioning
confidence: 99%
“…The analogous argumentation through increased expected severity may be applied to behavioural risk factors, such as smoking, excessive alcohol consumption, physical inactivity and unhealthy food intake but the empirical results showed either no association with the behavioural change or a negative effect depending on the preventive measures taken into consideration (Mendoza-Jiménez, Hannemann, & Atzendorf, 2021). Exposure to COVID-19 among the members of the social network was also argued to work through the pathway of perceived severity (Litwin & Levinsky, 2021).…”
Section: Theoretical Background and A Literature Reviewmentioning
confidence: 99%
“…Behavioural strategies for reducing COVID-19 transmission are constructive actions and thus they are expected to be positively correlated with conscientiousness and negatively with neuroticism. In the context of the COVID-19 pandemic, the studies on behaviour of older Europeans found that the conscientiousness and neuroticism were positively correlated with preventive measures (Litwin & Levinsky, 2021;Mendoza-Jiménez et al, 2021;Sand & Bristle, 2021). The results for extraversion, agreeableness, and openness were mixed and depended, among other, on the type of behaviour that was under consideration.…”
Section: Theoretical Background and A Literature Reviewmentioning
confidence: 99%